Fuzzy evaluation for response effectiveness in cases of incomplete information - Fenghua LI; Yongjun LI; Zhengkun YANG; Han ZHANG; Lingcui ZHANG (Tongxin xuebao)
In order to appropriately select and adjust response countermeasures,it is necessary to evaluate response effectiveness.Although a large amount of effort has been spent on the evaluation of risk and threat situations,the existing schemes are not suitable to evaluate response effectiveness,because the sechems require that all the information used for evaluation is complete,which is difficult to implement in the real environment.To address the problem,a fuzzy scheme was proposed to deal with incomplete information (i.e.,missing elements of judgment matrix and missing data of indicators) and the response effectiveness was evaluate.Firstly,a hierarchical indicator tree was design to characterize the effectiveness from the perspectives of both attack and defense.Then,the fuzzy analytic hierarchy process (FAHP) was used to calculate the comprehensive weight of each indicator.Finally,the response effectiveness was calculated using fuzzy comprehensive evaluation.In particular,to deal with the problem of incompleteness of fuzzy judgment matrix in the process of FAHP,the missing elements were completed based on the transitivity of elements.And to deal with the problem of loss data in the comprehensive evaluation,the missing data was completed based on matrix completion.The experimental results show that the proposed scheme can accurately recover the missing data and can effectively evaluate the effectiveness of response.